(3ebGdI aj GdWHs - (3CHh YHO Gddg eMeO Hf eMeO Hf Ydj Hf YHO Gddg GddNej GdTbhQj,J (B749 (3g` s
(3ChdgG (B:s
(3SCdJfi CeOc Gddg HCfhGQ GdMceI ceG CeOc HCfhGQ GdYde hLYdc GdaQM Gdeedi , hGdJGL ai SGHb Gdage s
(3BNQgG (B:s
(3hdLGdjfhS ai Pdc McGjI ai VeGO UfYg hWHjN SGb GdNfRjQ , hJYLH ef aYdg heG XgQ efg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B46 - (3U(B54(3Hs
(3GdeDda cGf MjG SfI (B749(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B285 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B71s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B248 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs